2016
DOI: 10.1016/j.rbre.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose positron emission tomography and serum cytokines and matrix metalloproteinases in the assessment of disease activity in Takayasu's arteritis

Abstract: Higher serum IL-6 and TNFα levels as well as higher (18)F-FDG uptake in arterial wall are associated with active TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Serum levels of IL‐6 were demonstrated to be positively related to disease activity in several studies. Arraes et al . found that serum IL‐6 levels were significantly higher in TA patients and had a positive relationship with disease activity.…”
Section: Biomarkerssupporting
confidence: 61%
“…Serum levels of IL‐6 were demonstrated to be positively related to disease activity in several studies. Arraes et al . found that serum IL‐6 levels were significantly higher in TA patients and had a positive relationship with disease activity.…”
Section: Biomarkerssupporting
confidence: 61%
“…In the majority of papers, patients with active disease presented with higher ESR and CRP levels as compared with patients with stable/inactive disease (ESR ranged 5–115 mm/hour vs 1–43 mm/hour and CRP ranged 0.1–99.1 mg/dL vs 0.06–7.77 mg/dL for active vs stable disease, respectively). Nevertheless, 28.5% of patients classified as being in remission (National Institutes of Health (NIH) criteria) may present with elevated CRP and 23.8% with elevated ESR23 (overall LoE 4) 23–29…”
Section: Resultsmentioning
confidence: 99%
“…Circulating interleukin (IL)-628 31–33 and IL-1831 levels of patients with active disease tend to be higher than of those with stable, inactive disease or healthy controls. In paired samples of patients who had active disease and then evolved to a stable stage, ESR and IL-18 significantly decreased and the changes in ESR correlated well with those of serum IL-18 levels (r=0.61, p<0.001) 31.…”
Section: Resultsmentioning
confidence: 99%
“…Disease activity in TA can be inferred from increased levels of serum IL-6 and TNFα and a higher uptake of 18F-Fluorodeoxyglucose [(18)F-FDG] in the arterial wall (25,22); even so, distinguishing between systemic and vascular inflammation is difficult and various evaluations have been suggested towards this end: The Indian Takayasu Clinical Activity Score (12), while other authors have recommended direct imaging of vessel wall thickening (ultrasound, CT, angiogram) or positron emission tomography computerized tomography (PET CT) (11).…”
Section: Discussionmentioning
confidence: 99%